2016
DOI: 10.1186/s13256-016-0884-9
|View full text |Cite
|
Sign up to set email alerts
|

Internal jugular venous thrombosis due to Trousseau’s syndrome as the presenting feature of metastatic prostate carcinoma: a case report

Abstract: BackgroundInternal jugular vein thrombosis is a rare vascular event with a potentially fatal outcome. Of the known etiologies, internal malignancies, either known or occult, are well described. Even though malignancies are known to present with internal jugular vein thrombosis, it rarely occurs due to prostate carcinoma. Many cases of jugular vein and superior vena cava thrombosis secondary to malignancies are due to metastatic compression of veins. Recurrent and unusual vascular thrombosis due to hypercoagula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Bilateral IJV thrombosis is extremely rare and can be an indicator of early malignancy. 5 Bandara et al 6 reported that hidden malignancy should be investigated in patients with spontaneous IJV thrombosis. In a study conducted on IJV thrombosis involving 41 cases conducted by Hahn et al, 7 the cause was found to be malignancy in 22 (53.6%) patients, inflammatory diseases such as cervical abscess in 14 (34.1%) patients, and insertion of a central venous catheter in 2 (4.8%) patients, while no cause was identified in 3 (7.3%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral IJV thrombosis is extremely rare and can be an indicator of early malignancy. 5 Bandara et al 6 reported that hidden malignancy should be investigated in patients with spontaneous IJV thrombosis. In a study conducted on IJV thrombosis involving 41 cases conducted by Hahn et al, 7 the cause was found to be malignancy in 22 (53.6%) patients, inflammatory diseases such as cervical abscess in 14 (34.1%) patients, and insertion of a central venous catheter in 2 (4.8%) patients, while no cause was identified in 3 (7.3%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing age, obesity, and associated illness have also been attributed as causes. External compression over the vein has also been reported as a possible cause [1, 4, 69]. …”
Section: Discussionmentioning
confidence: 99%
“…A later retrospective study demonstrated PE rates of 0.5% and 2.4% for isolated IJV thrombosis and combined subclavian/axillary vein and IJV thrombosis, respectively [68]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the increased risk of potentially fatal thromboembolic events, patients with internal jugular vein thrombosis receive full therapeutic anticoagulation. 13 , 14 The risk of propagation and embolization in patients with EJ thrombosis is less clear, but further thrombosis is possible. 9 However, most instances of this occur within the first few days of onset.…”
Section: Discussionmentioning
confidence: 99%